PENINGKATAN HASIL BELAJAR SISWA PADA MATERI GAYA MELALUI METODE DEMONSTRASI PADA SISWA KELAS V MADRASAH IBTIDAIYAH YAMINAS LOPPE KABUPATEN LUWU - Malasari Malasari (Fakultas Tarbiyah dan Ilmu Keguruan, 2019)
This study aims to improve science learning outcomes in the style material of fifth grade students of Yaminas Loppe Madrasah Ibtidaiyah Luwu Regency. The study was a type of Classroom Action Research (CAR) conducted in class V of Madrasah Ibtidaiyah Yaminas Loppe in Bupon Subdistrict, Luwu Regency with a total of 15 students. Data collection techniques used are observation, learning outcome tests, documentation. The results of this study indicate that the application of the demonstration method in science subjects style material can improve student learning outcomes of class V. This is shown through the acquisition of observations of student and teacher activities and test results that indicate an increase. The results of observation of student activities increased from 76.51 in the first cycle to 92.42 in the second cycle. Likewise, the observation of teacher activities also increased from 80 in the first cycle to 93.33 in the second cycle. Both the first and second cycle categories increased from good to very good. While the average test results increased from 61 included in the less category in the first cycle to 75.67 included in the sufficient category in the second cycle. Thus, indicators of success in research on classroom action are achieved. Thus by applying the demonstration method can improve science learning outcomes in elementary schools, especially material style material.